2004
DOI: 10.1002/pssc.200405431
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of Fe nanowires encapsulated in carbon nanotube

Abstract: We have investigated the electronic structures and magnetism of Fe nanowires encapsulated in carbon nanotube. We have calculated the magnetic moment, spin polarization, and conductance channel for Fe nanowires encapsulated in carbon nanotube. The magnetic moment of an encapsulated system is decreased compared with that of freestanding Fe nanowires and the spin polarization and conductance channel are also decreased. The decrease of magnetic moment and spin polarization is caused by a strong hybridization betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the theoretical respect, density functional theory (DFT) study has been reported on transition-metal (TM) filled carbon nanotubes. Strong spin polarization is predicted in Co, Ni, and Fe nanowires encapsulated inside single-walled carbon nanotubes (SWCNTs) as well as considerable magnetic moments. Recently, Parq et al compared the structural properties of four-atom pure Gd nanowire and Gd-carbide nanowires encapsulated in the (14,0) SWCNT, and suggested that the observed four-atom Gd chain encapsulated inside CNTs experimentally is a pure planar square Gd nanowire based on the fact that the calculated planar Gd−Gd distance in the pure Gd chain is consistent with the measured distance.…”
Section: Introductionmentioning
confidence: 99%
“…In the theoretical respect, density functional theory (DFT) study has been reported on transition-metal (TM) filled carbon nanotubes. Strong spin polarization is predicted in Co, Ni, and Fe nanowires encapsulated inside single-walled carbon nanotubes (SWCNTs) as well as considerable magnetic moments. Recently, Parq et al compared the structural properties of four-atom pure Gd nanowire and Gd-carbide nanowires encapsulated in the (14,0) SWCNT, and suggested that the observed four-atom Gd chain encapsulated inside CNTs experimentally is a pure planar square Gd nanowire based on the fact that the calculated planar Gd−Gd distance in the pure Gd chain is consistent with the measured distance.…”
Section: Introductionmentioning
confidence: 99%
“…A calculation on the magnetism of Fe NW wrapped by armchair CNT [4] showed that the magnetic moment was larger than that of bulk Fe. In particular, linear Fe NW with the bond length of 2.46 Å encapsulated in (5,5) CNT had a magnetic moment which is almost equal to that of freestanding NW, which is due to long Fe-C distance of 3.38 Å and nearly no interaction between the Fe NW and surrounding CNT.…”
Section: Introductionmentioning
confidence: 99%